Pengembangan Sumber Daya Guru Dalam Meningkatkan Kompetensi Pedagogis Melalui MGMP (Study di MTSS Sulamul Irfan Cibaliung-Pandeglang) - Tatang Abdurahman; Rijal Firdaus; Agus Gunawan (Journal on Education, 2023)
Educators are one of the most supportive factors in student learning activities. The existence of professional educators can ensure that the quality of learning in schools increases, with the professional title of the educator will always be able to improve teaching and learning activities will also add to the learning that has good quality. Human resources (HR) training can solve the problems of various students, teachers, lecturers, education staff and other employees in the field of education. Teacher quality development is an effort by educational institutions to improve teacher professionalism, through the development of various teacher skills and qualifications and one direction between policymakers to educators and education staff to increase the resource capacity of educators. Efforts to optimize teacher performance are currently an important factor in improving the quality of education relative to other factors. This is implemented by the government by teacher.